Exceptional abilities in the spatial representation of numbers and time: insights from synesthesia. - Cohen Kadosh, R; Gertner, L; Terhune, D (2012)
In the study of basic and high-level cognitive functions, neuroscientists, psychologists, and philosophers have tended to focus on normal psychological processes and on deficits in these processes, whereas the study of exceptional abilities has been largely neglected. Here the authors emphasize the value of researching exceptional abilities. They make the case that studies of exceptional representations, such as of time, number, and space in synesthesia, can provide us with insights regarding the nature of the neurocognitive mechanisms of these dimensions, as well as their developmental, evolutionary, and cultural origins.